Flexible Magnetic Sensors - Lili Pan; Yali Xie; Huali Yang; Mengchao Li; Xilai Bao; Jie Shang; Run-Wei Li (Sensors)
With the merits of high sensitivity, high stability, high flexibility, low cost, and simple manufacturing, flexible magnetic field sensors have potential applications in various fields such as geomagnetosensitive E-Skins, magnetoelectric compass, and non-contact interactive platforms. Based on the principles of various magnetic field sensors, this paper introduces the research progress of flexible magnetic field sensors, including the preparation, performance, related applications, etc. In addition, the prospects of flexible magnetic field sensors and their challenges are presented.